A CMOS-based light modulator for contactless data transfer: theory and concept - Serb,A; Nikolic,K; Constandinou,TG (SPIE, 2011)
A new technique pertaining to the optical contactless chip-to-board communication using a commercially available CMOS technology is under development. The main concept is to use mid-IR light from a small LED which will enter an IC from the underside, impinge upon one or more pn-junctions and be reflected by a metallic sheet so that it falls on an external, discrete photodetector. After propagation through the doped semiconductor, the light undergoes attenuation due to free carrier absorption. By varying the reverse bias across the pn-junction(s), the depletion region widths are changed and therefore modulation of light intensity can be achieved. Through this scheme, data readout can be realized optically, thus alleviating the need for galvanic contacts (most notably wirebonds).